Integrating TRIZ in Project Management Processes: An ARIZ Contribution. (2015) - Navas, Helena V.G.; Tenera, Alexandra M.B.R.; Machado, Virgílio A. Cruz
Abstract: Organizations are living in a constant change environment; their business and finance aims are very demanding. Project management faces up to a lot of problems and challenges. Project management community needs appropriate and efficient management practices. Generation of innovative ideas and solutions can give considerable contribution to project success; can bring efficacy and efficiency to organizations and markets. Without innovation, many organizations and its projects can be doomed to failure. The generation of ideas and systematical innovation is crucial to the project competitiveness. TRIZ methodology can contribute to the definition of the best project structure. TRIZ analytical tools can be very useful to problem solving in project management. TRIZ has been developed with special emphasis on product problems and product improvement. However, TRIZ is also used for process problem solving, so it can be useful for all project management issues and activities. This paper attends to applicability of TRIZ and its analytical tools (namely ARIZ) in project management processes. A new approach was proposed. Its main achieved results and expected impacts are exemplified on a case study.